Global longitudinal strain and plasma biomarkers for prognosis in heart failure complicated by diabetes: a prospective observational study - Iyer, Nithin R. (2024)
Background: Heart failure (HF) and diabetes are associated with increased incidence and worse prognosis of each other. The prognostic value of global longitudinal strain (GLS) measured by cardiovascular magnetic resonance (CMR) has not been established in HF patients with diabetes. Methods: In this prospective, observational study, consecutive patients (n = 315) with HF underwent CMR at 3T, including GLS, late gadolinium enhancement (LGE), native T1, and extracellular volume fraction (ECV) mapping. Plasma biomarker concentrations were measured including: N-terminal pro B-type natriuretic peptide(NT-proBNP), high-sensitivity troponin T(hs-TnT), growth differentiation factor 15(GDF-15), soluble ST2(sST2), and galectin 3(Gal-3). The primary outcome was a composite of all-cause mortality or HF hospitalisation. Results: Compared to those without diabetes (n = 156), the diabetes group (n = 159) had a higher LGE prevalence (76 vs. 60%, p < 0.05), higher T1 (1285±42 vs. 1269±42ms, p < 0.001), and higher ECV (30.5±3.5 vs. 28.8±4.1%, p < 0.001). The diabetes group had higher NT-pro-BNP, hs-TnT, GDF-15, sST2, and Gal-3. Diabetes conferred worse prognosis (hazard ratio (HR) 2.33 [95% confidence interval (CI) 1.43–3.79], p < 0.001). In multivariable Cox regression analysis including clinical markers and plasma biomarkers, sST2 alone remained independently associated with the primary outcome (HR per 1 ng/mL 1.04 [95% CI 1.02–1.07], p = 0.001). In multivariable Cox regression models in the diabetes group, both GLS and sST2 remained prognostic (GLS: HR 1.12 [95% CI 1.03–1.21], p = 0.01; sST2: HR per 1 ng/mL 1.03 [95% CI 1.00-1.06], p = 0.02). Conclusions: Compared to HF patients without diabetes, those with diabetes have worse plasma and CMR markers of fibrosis and a more adverse prognosis. GLS by CMR is a powerful and independent prognostic marker in HF patients with diabetes.